PENAMBAHAN SORBITOL SEBAGAI PLASTICIZER DALAM PEMBUATAN EDIBLE FILM PATI SUKUN - Putra, Anugerah Dwi; Johan, Vonny Setiaries; Efendi, Raswen (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Edible film is a thin layer of edible material placed on the surface of food products to provide a barrier for moisture, oxygen and solid transfer of the food. The main raw material in making edible film is breadfruit starch, chitosan as stabilizer and sorbitol as plasticizer. Theaimed of this research was to determine the effect sorbitol addition as a plasticizer to the quality of edible film and determine the proper concentration of sorbitol to produce an elastic and not fragile edible film. This research used a completely randomized design (CRD) with five treatments (without sorbitol, 0.4%, 0.8%, 1.2% and 1.6%) and four replications. The result showed that the best sorbitol concentration was S1 (0.4%) with thickness 0.21mm, The rate of water vapor transmission 462.11 g/m2/24 h, tensile strength 10.33 Mpa and elongation 5.29%.Keywords: edible film, sorbitol, plasticizer, breadfruit starch.